2021
DOI: 10.1021/acssynbio.1c00049
|View full text |Cite|
|
Sign up to set email alerts
|

Enabling Biological Nitrogen Fixation for Cereal Crops in Fertilized Fields

Abstract: Agricultural productivity relies on synthetic nitrogen fertilizers, yet half of that reactive nitrogen is lost to the environment. There is an urgent need for alternative nitrogen solutions to reduce the water pollution, ozone depletion, atmospheric particulate formation, and global greenhouse gas emissions associated with synthetic nitrogen fertilizer use. One such solution is biological nitrogen fixation (BNF), a component of the complex natural nitrogen cycle. BNF application to commercial agriculture is cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 59 publications
0
27
2
Order By: Relevance
“…In another study, CRISPR/Cas9 triple knockout of pyl1 , pyl4 , and pyl6 , OsPYL abscisic acid receptor gene family displayed high-temperature tolerance, increased grain yield, and lower preharvest sprouting in comparison to wild type ( Miao et al., 2018 ). Genome-edited crops contribute towards improved water and nitrogen use efficiency as demonstrated through field trial and experimental data ( Wen et al., 2021 ). Research on enhanced drought tolerance of cotton developed through genome editing tools demonstrated environmental footprint of cotton production ( Peng et al., 2021 ).…”
Section: Genome Editing In the New Era As A Promising Solution For Cr...mentioning
confidence: 99%
“…In another study, CRISPR/Cas9 triple knockout of pyl1 , pyl4 , and pyl6 , OsPYL abscisic acid receptor gene family displayed high-temperature tolerance, increased grain yield, and lower preharvest sprouting in comparison to wild type ( Miao et al., 2018 ). Genome-edited crops contribute towards improved water and nitrogen use efficiency as demonstrated through field trial and experimental data ( Wen et al., 2021 ). Research on enhanced drought tolerance of cotton developed through genome editing tools demonstrated environmental footprint of cotton production ( Peng et al., 2021 ).…”
Section: Genome Editing In the New Era As A Promising Solution For Cr...mentioning
confidence: 99%
“…[ 52 ]. Current advances in engineering root-associated diazotrophs [ 53 ] and the prospects of implementing N2-fixation in plants [ 54 , 55 ] can deliver new species (or their combination thereof) improved in their ability to capture atmospheric carbon into their biomass and expanding the green cover of our planet. Alas, this is not the end of the challenge: much of the vegetal matter can subsequently decay and be degraded by microorganisms which may release CO 2 back to the atmosphere.…”
Section: The Players Of Global Carbon Balancementioning
confidence: 99%
“…A potentially promising avenue represents the editing of the genome of bacterial strains via synthetic biology to increase their N fixation capacity under field condition and to render a commercial application as bio-fertilizers a successful endeavour. Such an approach was reported for a free-living strain of Klebsiella variicola , where the authors replaced the nifL gene, which usually represses N fixation under conditions of sufficient N availability, with a constitutive promoter to obtain a strain that could still fix N under field conditions (Wen et al 2021 ). In a number of trials where the strain was applied in addition to inorganic fertilizers in corn fields, increased yields of around 3% and lower within-field yield variance were observed as compared to fields that were only subjected to inorganic fertilization.…”
Section: Plant Nutritionmentioning
confidence: 99%